Comparison of the accuracy of cone-beam computed tomography, photostimulable phosphor imaging plate, charge coupled device, and conventional intraoral radiography in the diagnosis of internal root resorption: an in vitro study - Abbas Shokri; Jalal Poorolajal; Farhad Faramarzi (Brazilian Dental Science)
Objective: Various radiographic methods are used to identify the internal root resorption. The aim of this study was to assess and compare the diagnostic accuracy of cone-beam computed tomography (CBCT), photostimulable phosphor (PSP) imaging plate, charge coupled device (CCD), and conventional intraoral radiography (CIR), for internal root resorption.